The Sentiment Analysis of Spider-Man: No Way Home Film Based on IMDb Reviews - Putu Harry Gunawan; Tb Dzulfiqar Alhafidh; Bambang Ari Wahyudi (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2022)
Sentiment analysis is used to determine the overall sentiment in a movie review. The goal of this paper is to investigate the sentiment analysis using multiple classification methods from Spider-Man: No Way Home movie reviews. The review dataset is procured from the IMDb website. Preprocessing methods are used and compared to determine the difference in accuracy score. The methods proposed for this study include Naïve-Bayes, Support Vector Machine (SVM), Stochastic Gradient Descent (SGD), and Decision Tree to find the best accuracy possible. The sentiment analysis of the movie review resulted in 94 positive reviews and 65 negative reviews. The highest accuracy and f1 score for this study are obtained from the SVM and the SGD classifier with an accuracy of 82% and an F1 score of 81% respectively